When are puppies receptive to emotion-induced human chemosignals? The cases of fear and happiness - D’Aniello, Biagio; Pinelli, Claudia; Scandurra, Anna; Di Lucrezia, Alfredo; Aria, Massimo; Semin, Gün R. (Animal cognition, 2023)
We report an observational, double-blind, experimental study that examines the effects of human emotional odors on puppies between 3 and 6 months and adult dogs (one year and upwards). Both groups were exposed to control, human fear, and happiness odors in a between subjects’ design. The duration of all behaviors directed to the apparatus, the door, the owner, a stranger, and stress behaviors was recorded. A discriminant analysis showed that the fear odor activates consistent behavior patterns for both puppies and adult dogs. However, no behavioral differences between the control and happiness odor conditions were found in the case of puppies. In contrast, adult dogs reveal distinctive patterns for all three odor conditions. We argue that responses to human fear chemosignals systematically influence the behaviors displayed by puppies and adult dogs, which could be genetically prefigured. In contrast, the effects of happiness odors constitute cues that require learning during early socialization processes, which yield consistent patterns only in adulthood.